Identified Human Factors in Knowledge Management in the Context of Knowledge Sharing (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the present and advances in information and communication technology (ICT), sharing knowledge across organisations has become easier and feasible. However, knowledge sharing has been a complex phenomenon over the years and identifying factors that influence knowledge sharing (KS) across organisation has becomes crucial and critical in the recent days. This paper review the effect of culture and behavioural differences as a human factors and the knowledge management practices needed to improve KS in organisations. Data were collected from 7 experts and 50 personnel by questionnaire. The result from the statistical data analysis revealed 15.67 and 3.96 as variance and standard deviation on culture respectively. The variance on behaviour is 8 and its standard deviation is 2.83, this indicate weakness in KS therefore, there is a presence of non- sharing culture and behaviour that discourage knowledge sharing. The findings from this pilot study suggest that, a centralised knowledge management structure without effective human practice towards its policies of sharing, coordination and distribution of knowledge in the context of knowledge management towards knowledge sharingmight fail. For organisation to avoid knowledge holding (KH) and knowledge risk (KR), a mechanism like knowledge sharing strategic implementation plan (KSSIP) can be used as a solution.